العلاقة الدبلوماسية بين المماليك والإمبراطورية البيزنطية 660 هـ.-815 هـ. = 1261 م.-1412 م. - حسن، غادة (جامعة تشرين, 2020)
تهدف هذه الدراسة إلى بحث العلاقات الدبلوماسية بين المماليك والبيزنطيين، وتحاول توضيح الدوافع والأسباب لقيام هذه العلاقات، والوسائل المستخدمة في ذلك وهي السفارات والمراسلات والمعاهدات. كما يهدف البحث إلى معرفة الأهداف السياسية والاقتصادية والدينية التي أراد كل منهما تحقيقها من خلال هذه الوسائل، والنتائج التي نجمت عن تلك العلاقات.
This study aims to examine diplomatic relations between the Mamluks and the Byzantines; it tries to clarify the motives and reasons for establishing these relations, the means used in this, which are embassies, correspondence and treaties. The research also aims to know the political, economic and religious goals that each of them wanted to achieve through these means, and the results that resulted from those relations.
Keywords: الإمبراطورية البيزنطية -- دولة المماليك -- العلاقات الدبلوماسية